2021
DOI: 10.1242/jeb.238899
|View full text |Cite
|
Sign up to set email alerts
|

Experience, but not age, is associated with volumetric mushroom body expansion in solitary alkali bees

Abstract: In social insects, changes in behavior are often accompanied by structural changes in the brain. This neuroplasticity may come with experience (experience-dependent) or age (experience-expectant). Yet, the evolutionary relationship between neuroplasticity and sociality is unclear, because we know little about neuroplasticity in the solitary relatives of social species. We used confocal microscopy to measure brain changes in response to age and experience in a solitary halictid bee (Nomia melanderi). First, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“… 19 ) are required to determine to what extent brain development between the newly emerged daughter and foundress stages is age vs. experience dependent. While our study was not designed to explicitly test for experience-expectant plasticity, this result is consistent with the two other studies of solitary bees which showed no experience-expectant plasticity 19 , 23 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“… 19 ) are required to determine to what extent brain development between the newly emerged daughter and foundress stages is age vs. experience dependent. While our study was not designed to explicitly test for experience-expectant plasticity, this result is consistent with the two other studies of solitary bees which showed no experience-expectant plasticity 19 , 23 .…”
Section: Discussionsupporting
confidence: 90%
“…Workers instead accrue indirect fitness by helping the colony reproduce throughout their lives. The only studies to examine the development of brain structures of solitary or small-colony bees either used individuals still engaged in reproduction 15 , 18 , 23 , 28 or tropical species with no distinct end to the reproductive season 27 , 31 . Likewise, studies demonstrating experience-based enlargement of the MB in Lepidoptera also did not include post-reproductive individuals 13 , 14 , 51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future work comparing sex-specific patterns of brain development in additional bee species is needed to determine the pervasiveness of intersexual differences in neuroplasticity. Investigating socioecological drivers of neuroplasticity in both sexes, particularly in solitary species where females lack age-related plasticity 57 , 58 , will provide a more robust understanding of the relationship between neuroplasticity and social evolution.…”
Section: Discussionmentioning
confidence: 99%